Moral change and the purchase-sale relationship: Critical analysis of Swiss and German companies - Marco Schmaeh; Allessandro Siblio; Patrick Höra; Jessica Sager; Leon Winter; Benjamin Schwegler (International Journal of Business and Social Science Research, 2022)
This study examines the awareness and causes of moral change from the economic perspective in Germany and Switzerland. Based on an analysis of value research to date and interviews with experts in B2B sales, the manifestations of moral change are critically examined and recommendations for action are derived on an employee-specific and company-wide level.